Superior toughened bio-compostable Poly(glycolic acid)-based blends with enhanced melt strength via selective interfacial localization of in-situ grafted copolymers. (19th November 2021) - Niu, Deyu; Xu, Pengwu; Sun, Zhaoyang; Yang, Weijun; Dong, Weifu; Ji, Yang; Liu, Tianxi; Du, Mingliang; Lemstra, Pieter Jan; Ma, Piming
Abstract: As an emerging bioplastic, poly(glycolic acid) (PGA) possesses excellent bio-compostability, gas barrier properties, mechanical strength and heat resistance. However, the inherent brittleness and inferior melt-strength of PGA severely limits its processability and application possibilities. In the present contribution, a two-step reactive melt blending of PGA and poly(butylene adipate-co-terephthalate) (PBAT) with epoxy functionalized copolymer (ethylene-methyl acrylate-glycidyl methacrylate) (EMAG) as compatibilizer was investigated to solve these shortcomings. The EMAG was first blended with PBAT and then with PGA to in-situ form PGA-g-EMAG-g-PBAT copolymers. These copolymers selectively locate at the interface between PGA and PBAT, which effectively improved the interfacial adhesion and the compatibility. Consequently, the PGA/(PBAT/EMAG) blends with 1 wt % EMAG exhibited high elongation at break (45 ± 4%) and a notched impact strength (14.4 ± 1.6 kJ/m 2 ) respectively, which is about 1100% and 410% higher than that of PGA. Meanwhile, the viscosity and storage modulus of the PGA/(PBAT/EMAG) blends at 50.1 Hz were enhanced by 130% and 230% compared with PGA. This work provides a facile route to fabricate PGA-based blends with excellent toughness and melt strength, which could open up new possibilities for the application of PGA materials. Graphical abstract: Image 1 Highlights: Bio-compostable poly(glycolic acid)-based blends were prepared by reactive melt blending. Two-step blending processes was used to control the interfacial localization of in-situ grafted copolymers. Interface-localized copolymers markedly enhance interfacial adhesion and compatibility between PGA and PBAT. PGA/(PBAT/EMAG) blends exhibited much superior toughness and melt strength than PGA.